Magnetism and Gravity: Mental representations of students 15-17 years old from a historical and teaching perspective - Ravanis, Konstantinos; Voutsina, Lambrini (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
In the present paper we will study the mental representations of students aged 15-17 concerning action at a distance based on the manner of transfer of the magnetic force as well as the relation between magnetism and gravity. The research was carried out using structured interviews with a total of 40 students from the 10th and 11th grades. We will also attempt to study whether the students representations show an analogical reasoning with typical historical models of the Sciences and whether there exist differences related to conventional school teaching. The results indicated points where students representations appear to approach basic elements of historical models of the Sciences.